Modul Crosstalk Untuk Mata Kuliah Praktikum EMC - Harpawi, Noptin; M Yanuar Hariyawan; M Susantok (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
To get a small PCB size, it is important to put the tracks close together. When a track carries a high frequency signal (EMI source track), then the signal on that track will affect signals on other tracks, which is called the crosstalk phenomenon. The affected track is called the victim track. The result of this phenomenon is the damage to the signal on the victim track. So that the load on the victim track will receive a different signal form compared to the signal form from the source. To see this phenomenon, a module is made which consists of various configurations between the emi source track and the victim track. This configuration is distinguished by the distance between the emi source track and the victim tract, the width of the two tracks, and the length of the parallel path between the two tracks. Based on the test scenario that has been planned, the results of this study show that the highest emission value on the victim occurs when the distance between the tracks is 1 mm, the track width is 10 mm, and the length of the parallel path between the tracks is 95 mm. When the source track is given a square signal with an amplitude of 2.84 V, a frequency of 2.5 MHz, emission is obtained on the victim track is 156 mV (Near End) and 146 mV (Far End). Keywords: Crosstalk, EMC, Victim